The Theological Interpretation of Scripture: Recent Contributions By Stephen E. Fowl, Christopher R. Seitz and Francis Watson - Cummins, S.A. (2004)
In the midst of the massive enterprise that is contemporary biblical scholar ship there has emerged in recent years an interest in recovering and rede ploying a distinctly theological approach to biblical interpretation. By way of introduction to certain significant aspects of this undertaking, this issue- orientated article considers the contribution of three important partici pants: Stephen E. Fowl, Christopher R. Seitz and Francis Watson. Matters under review include defining theological interpretation, its critique of cer tain historical-critical approaches, its attempts to work within a trinitarian framework, its concern to integrate the Old Testament more fully into a two-testament account of Scripture, and its interest in the role of the inter preting Christian community. In this way the article acknowledges and invites further engagement with an important and invigorating development within biblical and theological studies.